Impact of Mergers and Acquisitions on Corporate Stakeholder Practices in Nepalese Commercial Banks - Verma, Rahul Kumar (Nepalese Journal of Management, 2024)
This study examines the impact of mergers and acquisitions on corporate stakeholder practices in Nepalese commercial banks. Bank performance is the dependent variable. The selected independent variables are reward system, employee’s performance, career development, job security, and technology and development. The primary source of data is used to assess the opinions of respondents regarding reward system, employee’s performance, job security, career development, technology and development. The study is based on primary data of 121 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of impact of mergers and acquisitions on corporate stakeholder practices in Nepalese commercial banks.The study showed a positive impact of reward system on bank performance. It indicates that providing good remuneration convenience to the employees leads to increase in bank performance. Similarly, the study showed a positive impact of employee’s performance on bank performance. This indicates that higher the employee’s performance, higher would be the bank performance. The study also revealed a positive impact of job security on bank performance. It indicates that high job security leads to increase in bank performance. Likewise, the study observed a positive impact of career development on bank performance. It indicates that career development leads to increase in bank performance. Further, the study observed a positive impact of technology and development on bank performance. It indicates that advance technology and development leads to increase in bank performance. It indicates that the advancement in technology enhance the bank performance.